Geotechnical aspects of pavements : reference manual / participant workbook - Christopher, Barry R. 1949- (U.S. Dept. of Transportation, Federal Highway Administration : National Highway Institute, 2006)
This 2006 manual covers the latest methods andprocedures to address the geotechnical issues in pavement design, construction andperformance for new construction, reconstruction, and rehabilitation projects.